Factors Underlying Adoption of Rice Power-Threshers in West Sumatera - Masdjidin Siregar (Jurnal Agro Ekonomi, 1986)
Since the use of threshers in post harvest operation has shown promise of providing higher technical as well as allocative efficiency, this study was focused primarily on how such a device could be adopted and diffused more rapidly in response to the government's emphasis on rice quality improvement. Not only was this study interested in farmer's constraints to adopt such a technology, but it also investigated the role of innovating agents as well as the institutional nature of rural labor relation in the adoption process. The former has been analyzed by fitting logistic regression procedure towards data of 75 farmers in six villages while the latter is presented in the form of comparison between West Sumatera and Java.